Comparing Cephalic Index and Midsagittal Vector Analysis in Assessing Morphology in Sagittal Synostosis: A CT-Based Morphometric Analysis. (August 2019) - Hong, Brian Y.; Ho, Emily S.; Zellner, Elizabeth; Phillips, John H.; Forrest, Christopher R.
Introduction: Assessment of cranial dysmorphism in sagittal synostosis is often subjective but objective measures can be applied. These include cephalic index (CI) and midsagittal vector analysis (MSVA). Objective: To assess discriminant validity, construct validity, and responsiveness of CI and MSVA measured from computed tomography (CT) in patients with sagittal synostosis. Methods: Patients with nonsyndromic isolated sagittal synostosis with complete preoperative (n = 30) and postoperative (n = 13) CT data were included. Age-matched control group (n = 24) comprised of normocephalic patients who underwent CT for reasons related to trauma. Outcome Measures: Retrospective CT evaluation of CI and MSVA was conducted and correlated with a dysmorphism numeric rating scale (D-NRS) that measured surgeon-rated severity of sagittal synostosis. Responsiveness of CI and MSVA was evaluated using dysmorphism global rating of change (D-GRC). Results: Thirty patients with sagittal synostosis were demographically similar to 24 normocephalic patients. The difference in CI and MSVA was statistically significant between normocephalic and scaphocephalic patients. Cephalic index had a good correlation with D-NRS ( r = −0.665, ρ = −0.667), but not with MSVA ( r = 0.250, ρ = 0.203). Change in CI ( r = 0.738, ρ = 0.657) was well correlated with D-GRC, but not with MSVA ( r = −0.409, ρ = −0.301). Conclusion: Cephalic index appears to quantify the severity of sagittal synostosis better than MSVA. Cephalic index also has better responsiveness than MSVA to measure a reduction in severity of disease; however, MSVA is a better descriptive craniometric measurement. Midsagittal vector analysis was able to quantify the shift in morphology in sagittal synostosis following surgical treatment.